Analisis Saluran Distribusi Rantai Pasokan Padi di Desa Mruwak Dagangan Kabupaten Madiun - Wilis Herlin Aryani; Dilla Septia Islami; Aloysius Tommy Hendrawan (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Mruwak is one of the villages in Madiun Regency where the majority of residents work as farmers. The food commodity most widely grown in the village is rice, while the rest are corn, sweet potatoes and peanuts. With the existence of a supply chain system, it is hoped that it can help farmers determine rice marketing routes effectively and efficiently. The aim of this research is to determine the supply chain system for rice produced by farmers in Mruwak Village. This research is qualitative in nature and the sample was selected purposively and using snowball sampling. The research results show the rice process, starting from land processing, rice planting, to maintenance and harvest. The farmers in the village have experience in growing rice, on average they have been growing rice for more than 10 years so they understand how to grow rice properly, including selecting superior seeds. The supply chain distribution channel used is a simple distribution channel model (1 to 3 level distribution channel model). Determination of selling prices based on agreements between farmers and buyers through demand and supply mechanisms (market mechanisms).